Taxonomic debate: anthropological or philosophical problem? - Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2004)
Over the centuries, anthropology has been marked by periods of multiplication or reduction of the taxonomic names of the hominids. Repeatedly, anthropologists, examining the same hominid material, came to different conclusions and made its classification differently. It is therefore worth considering whether these taxonomic controversies result only from biological reasons, or rather from philosophical reasons. The positive answer to this question shows them the common research area of biological and philosophical sciences. Although the methodologies of these disciplines are different, and the type of questions and the scope of concepts are different, these sciences "cooperate" with each other on the basis of discussions about the origins of man.